The Effect of Plyometric Training on Increasing Ball Speed of Flying Shoot Technique in Training to Compete Phase - Febryana, Lenny; Hariadi, Imam; Fadhli, Nurrul Riyad (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This research aims to examine the effectiveness of plyometric exercises in improving ball speed in the flying shoot technique for handball athletes in Bojonegoro District during the training to compete phase. The research design for this study is the One-Group Pretest-Posttest Design, utilizing a pre-experimental design approach with a descriptive quantitative research method. The sample was taken using total sampling, consisting of 13 male handball athletes from Bojonegoro District. The instrument used in this study was a ball speed test. Normality testing was conducted using the Shapiro-Wilk test, and it was found that the pretest-posttest data for ball speed were normally distributed with a significance value of 0,151 for the pretest and 0,323 for the posttest, both greater than 0,05. Homogeneity testing using Levene's Test yielded a significance value of 0,320 > 0,05. Hypothesis testing using the T-Test resulted in a ball speed test score of 0,000 < 0,05. The study concludes that there is a significant impact of plyometric training on improving ball speed in the flying shoot technique for male handball athletes in Bojonegoro District during the training to compete phase.